2007
DOI: 10.1210/jc.2006-1525
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Predicts Physical Performance and Its Decline in Older Persons

Abstract: Context: Vitamin D deficiency is common among older people and can cause mineralization defects, bone loss, and muscle weakness.Objective: The aim of this study was to investigate the association of serum 25-hydroxyvitamin D (25-OHD) concentration with current physical performance and its decline over 3 yr among elderly. Design:The study consisted of a cross-sectional and longitudinal design (3-yr follow-up) within the Longitudinal Aging Study Amsterdam.Setting: An age-and sex-stratified random sample of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
387
2
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 531 publications
(423 citation statements)
references
References 39 publications
20
387
2
14
Order By: Relevance
“…Observational data have revealed that 25(OH)D levels predict the decline in bone mineralization and physical performance when 25(OH)D falls below 8 and 20 ng/mL (20 and 50 nmol/L), respectively 8, 56. Although the underlying mechanisms remain to be elucidated, vitamin D may represent a pathway by which bone and muscle may work together, enabling cross‐talk between these tissues ( Figure  3).…”
Section: Vitamin D Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Observational data have revealed that 25(OH)D levels predict the decline in bone mineralization and physical performance when 25(OH)D falls below 8 and 20 ng/mL (20 and 50 nmol/L), respectively 8, 56. Although the underlying mechanisms remain to be elucidated, vitamin D may represent a pathway by which bone and muscle may work together, enabling cross‐talk between these tissues ( Figure  3).…”
Section: Vitamin D Physiologymentioning
confidence: 99%
“…Vitamin D deficiency is common in patients with chronic kidney disease (CKD),4 a population in whom muscle wasting and weakness are also highly prevalent 5, 6, 7. Observational studies have shown that circulating 25‐hydroxyvitamin D [25(OH)D] levels are reduced in parallel to the severity of muscle symptoms 8. Similarly, emerging evidence suggests that vitamin D receptor (VDR) is expressed in muscle and that VDR regulates gene expression and modulates the uptake of 25(OH)D in skeletal muscle cells, which may also act as a storage site for this vitamin D 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3) Indeed, there is increasing evidence that when accounting not for skeletal health but the salutary effects of vitamin D on nonskeletal organs, the optimal health-promoting concentration of 25(OH)D is around 30 ng/mL. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) In particular, adverse neuromuscular events such as muscle weakness, balance impairment, and reduced nerve conduction have been described for serum 25(OH)D concentrations below 30 ng/mL. (3)(4)(5)(6)(7)(8)(9)(10)(11) Walking speed is a simple, objective performance-based measure of lower limb neuromuscular function that not only allows detection of subtle impairments and preclinical diseases but also is a sensitive marker of functional capacity in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) In particular, adverse neuromuscular events such as muscle weakness, balance impairment, and reduced nerve conduction have been described for serum 25(OH)D concentrations below 30 ng/mL. (3)(4)(5)(6)(7)(8)(9)(10)(11) Walking speed is a simple, objective performance-based measure of lower limb neuromuscular function that not only allows detection of subtle impairments and preclinical diseases but also is a sensitive marker of functional capacity in older adults. (10)(11)(12)(13)(14)(15)(16) For instance, Suzuki and colleagues recently demonstrated that walking speed in older adults was positively ORIGINAL ARTICLE J JBMR correlated with physical performance tests such as handgrip strength or stork standing time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation